2022
DOI: 10.3389/fphar.2021.794103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Effect of Metformin and Insulin on Gut Microbiota and Metabolome Profiles of Type 2 Diabetic Rats Induced by the Combination of Streptozotocin and High-Fat Diet

Abstract: Lately, an increasing number of studies have investigated the relationship between metformin and gut microbiota, suggesting that metformin exerts part of its hypoglycemic effect through the microbes. However, its underlying mechanism remains largely undetermined. In the present study, we investigated the effects of metformin on gut microbiota and metabolome profiles in serum and compared it with insulin treatment in rats with type 2 diabetes mellitus (T2DM). Diabetic rats (DM group) were induced by a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The metabolic disorder of phospholipid contributes to development of diabetes ( 45 ). It has been shown that LysoPC, lysoPE, and lysoPS are associated with diabetes-related inflammatory stress ( 18 , 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolic disorder of phospholipid contributes to development of diabetes ( 45 ). It has been shown that LysoPC, lysoPE, and lysoPS are associated with diabetes-related inflammatory stress ( 18 , 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic disorder of phospholipid contributes to development of diabetes ( 45 ). It has been shown that LysoPC, lysoPE, and lysoPS are associated with diabetes-related inflammatory stress ( 18 , 45 , 46 ). Therefore, the levels of lysoPC, lysoPE, and lysoPS significantly decreases after diabetes remission.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of insulin on gut microbiota in rats with T2DM was modest, only three genera were changed in the insulin treatment group as compared with the metformin group, where the relative abundances of 13 genera were significantly changed. In the insulin treated group, an increased abundance of norank_f_Bacteroidales_S24-7 _group and a decreased abundance of Lactobacillus and unclassified_f_Peptostreptococcaceae were observed [ 100 ].…”
Section: Microbiota and Therapy For Diabetes Mellitusmentioning
confidence: 99%
“…Increasing numbers of studies are investigating whether metformin exerts its hypoglycemic effect through the modulation of microbiome in the diabetic rat gut [ 71 ]. However, its underlying mechanism remains largely unclear, though it has been shown that DM leads to a higher Firmicutes/Bacteroidetes ratio in the gut microbiome that can be reverted by metformin [ 71 , 72 ].…”
Section: Pharmacological Treatment Of T2dmmentioning
confidence: 99%